Organizational behavior - Robbins, Stephen P., 1943-; Judge, Tim. (Boston : Pearson, 2017)
For undergraduate and graduate courses in Organizational Behavior. Help Students Better Understand Their Behavioral and Interpersonal Skills Long considered the standard for all organizational behavior textbooks, Organizational Behavior provides the research you want, in the language you can understand. This text continues its tradition of making current, relevant research come alive for readers. The Seventeenth Edition has been thoroughly updated to reflect the most recent research and business events within the field of organizational behavior worldwide, while maintaining its hallmark features-clear writing style, cutting-edge content, and intuitive pedagogy. There's a reason why Robbins's textbooks have educated millions of individuals and have been translated into twenty languages-and it's because of a commitment that provides the kind of engaging, cutting-edge material that helps readers understand and connect with organizational behavior. Also Available with MyManagementLabTM MyManagementLab is an online homework, tutorial, and assessment program designed to work with this text to engage students and improve results. Within its structured environment, students practice what they learn, test their understanding, and pursue a personalized study plan that helps them better absorb course material and understand difficult concepts. NOTE: You are purchasing a standalone product; MyManagementLab does not come packaged with this content. If you would like to purchase both the physical text and MyManagementLab search for: 0134437861/ 9780134437866 Organizational Behavior Plus MyManagementLab with Pearson eText -- Access Card Package Package consists of: 013410398X / 9780134103983 Organizational Behavior 0134182189 / 9780134182186 MyManagementLab with Pearson eText--Access Card--for Organizational Behavior.
Introduction. What is organizational behavior? -- The individual. Diversity in organizations ; Attitudes and job satisfaction ; Emotions and moods ; Personality and values ; Perception and individual decision making ; Motivation concepts ; Motivation : from concepts to applications -- The group. Foundations of group behavior ; Understanding work teams ; Communication ; Leadership ; Power and politics ; Conflict and negotiation ; Foundations of organization structure -- The organization system. Organizational culture ; Human resource policies and practices ; Organizational change and stress management -- Appendix: Research in organizational behavior -- Comprehensive cases -- Glossary.
Revised edition of Organizational behavior, 2015.
Includes bibliographical references and indexes.
Keywords: Organizational behavior; Corporate culture; Organizational Culture